Maxwell-Equations Based on Mining Transient Electromagnetic Method for Coal Mine-Disaster Water Detection - Su, Benyu; Yu, Jingcun; Sheng, Chenxing (Elektronika ir Elektrotechnika, 2017)
Water-bearing geological structure is a serious threat to coalmine safety. This research focuses on detecting water-bearing geological structure by transient electromagnetic method. First, we introduce the principle of mining transient electromagnetic method, and then explain the technique of Finite Different Time Domain using in the transient electromagnetic method. Based on Maxwell equations, we derive the difference equations of electromagnetic field and study the responses of water-bearing geological structure using FDTD. Moreover, we establish the relationship between receiving electromagnetic field and geological information. The typical coal geological model of goaf-water is chosen to do the numerical simulation. Besides, we verify the availability of the method by numerical simulation using coal geological model. Finally, we use the method in the coalmine which is located in Linfen city in Shanxi province in China, and the detecting result is verified by drilling. DOI: http://dx.doi.org/10.5755/j01.eie.23.3.18326